2020
DOI: 10.1111/cas.14294
|View full text |Cite
|
Sign up to set email alerts
|

Avelumab plus axitinib vs sunitinib for advanced renal cell carcinoma: Japanese subgroup analysis from JAVELIN Renal 101

Abstract: The phase 3 JAVELIN Renal 101 trial of avelumab + axitinib vs sunitinib in patients with treatment‐naive advanced renal cell carcinoma (RCC) demonstrated significantly improved progression‐free survival (PFS) and higher objective response rate (ORR) with the combination vs sunitinib. Japanese patients enrolled in the study (N = 67) were randomized to receive avelumab + axitinib (N = 33) or sunitinib (N = 34); 67% vs 59% had PD‐L1+ tumors (≥1% of immune cells) and 6%/64%/27% vs 6%/82%/12% had International Meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 33 publications
3
37
0
Order By: Relevance
“…In this phase 1b study of patients with locally advanced or metastatic HCC, avelumab in combination with axitinib had a manageable safety profile that was consistent with that of each treatment when administered as monotherapy or in combination [25,34,39,40]. The TRAE profile was also consistent with that observed in the avelumab plus axitinib arm (N = 434) of the large, randomized, phase 3 JAVELIN Renal 101 trial, in which the most common grade ≥3 TRAEs were hypertension (n = 106 [24.4%]), PPE syndrome (n = 25 [5.8%]), diarrhea (n = 22 [5.1%]), and alanine aminotransferase increased (n = 21 [4.8%]) [34], as well as in the subgroup of Japanese patients enrolled in the trial [35]. In the phase 3 JAVELIN Renal 101 trial, an AE led to discontinuation of both avelumab and axitinib in 33 patients (7.6%) [34].…”
Section: Discussion/conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this phase 1b study of patients with locally advanced or metastatic HCC, avelumab in combination with axitinib had a manageable safety profile that was consistent with that of each treatment when administered as monotherapy or in combination [25,34,39,40]. The TRAE profile was also consistent with that observed in the avelumab plus axitinib arm (N = 434) of the large, randomized, phase 3 JAVELIN Renal 101 trial, in which the most common grade ≥3 TRAEs were hypertension (n = 106 [24.4%]), PPE syndrome (n = 25 [5.8%]), diarrhea (n = 22 [5.1%]), and alanine aminotransferase increased (n = 21 [4.8%]) [34], as well as in the subgroup of Japanese patients enrolled in the trial [35]. In the phase 3 JAVELIN Renal 101 trial, an AE led to discontinuation of both avelumab and axitinib in 33 patients (7.6%) [34].…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…The randomized phase 3 JAVELIN Renal 101 trial of first-line avelumab plus axitinib versus sunitinib in advanced RCC demonstrated significantly improved PFS with the combination [34], including in Japanese patients [35], leading to regulatory approval of avelumab in combination with axitinib in the USA, European Union, and Japan for the first-line treatment of advanced RCC [25,36,37].…”
Section: Introductionmentioning
confidence: 99%
“…The ORR was 60.6 vs. 17.6%, respectively. Common TRAEs (grade ≥ 3) in each group were hand-foot syndrome (9 vs. 9%, respectively), hypertension (30 vs. 18%, respectively), and platelet count decreased (0 vs. 32%, respectively) ( 69 ). Given the bracing results of JAVELIN Renal 101 study, avelumab combined with axitinib was approved by FDA.…”
Section: Clinical Data Involving the Combination Of Anti-angiogenic Amentioning
confidence: 99%
“…The JAVELIN Renal 101 study demonstrated that the PD-L1 expression levels cannot distinguish whether the combination therapy benefits PFS, while the high levels of intratumoral CD8+ T cells were strongly associated with better efficacy. Notably, 26 gene profiles, including immune-related genes, may be potential biomarkers for this combination ( 69 ).…”
Section: Predictive Indicators For Combination Therapy Of Anti-angiogmentioning
confidence: 99%
“…Two new combination therapies consist of axitinib and ICIs. The combination is expected to provide a synergistic effect 8,9 , but information on outcomes of first-line axitinib monotherapy against mRCC in the subset of patients with favorable or intermediate IMDC risk scores is still needed.…”
mentioning
confidence: 99%